Synthesis of Spiro Oxazolidinedione Analogues Based on Tandem Multicyclizations of 1,3-Dimethylalloxan and Enaminones in Water - Abbasi, Tina; Teimouri, Mohammad Bagher; Yavari, Issa; Bikas, Rahman (Synlett, 2020)
A tandem double-annulation reaction of 1,3-dimethylalloxan with enaminones, generated in situ from alkyl amines and alkyl but-2-ynoates or pent-3-yn-2-ones to give functionalized oxazolidinedione spiro analogues is described. Three of the four carbonyl groups of alloxan have been engaged through a tandem Michael addition, aldol-type condensation, and double intramolecular annulation sequence.
Keywords: alloxan; enaminones; multicomponent reaction; oxazolidinediones; spiroheterocycles; tandem reaction